Ab initio calculation of anion proton affinity and ionization potential for energetic ionic liquids. Issue 9 (23rd January 2015) - Carlin, Caleb; Gordon, Mark S.
<x xml:space="preserve">Abstract</x> Developing a better understanding of the bulk properties of ionic liquids requires accurate measurements of the underlying molecular properties that help to determine the bulk behavior. Two computational methods are used in this work: second‐order perturbation theory (MP2) and completely renormalized coupled cluster theory [CR‐CC(2, 3)], to calculate the proton affinity and ionization potential of a set of anions that are of interest for use in protic, energetic ionic liquids. Compared with experimental values, both methods predict similarly accurate proton affinities, but CR‐CC(2, 3) predicts significantly more accurate ionization potentials. It is concluded that more time intensive methods like CR‐CC(2, 3) are required in calculations involving open shell states like the ionization potential. © 2015 Wiley Periodicals, Inc.